Peningkatan hasil belajar siswa kelas 5 SD terhadap mata pelajaran matematika melalui bimbingan belajar di Dusun Putuk, Poncokusumo - Rahmawati, Iin Nur Indah (Maliki Interdisciplinary Journal, 2024)
Education are the most basic and planned efforts to create an atmosphere of teaching and learning and the learning process so that students actively develop their potential to have religious spiritual strength, self control, personality, intelligence, noble character, and the skill needed by themselves, their society, nation, and state. One way to to achieve education is to do free tutoring. This is what KKM group 123 UIN Maulana Malik Ibrahim Malang did in Putuk Hamlet, Ngadireso Village, Poncokusumo District, Malang Regency. This study used a descriptive qualitative method and focused on fifth grade elementary school students. This free tutoring was held with the aim of increasing learning outcomes and overcoming problems in learning for elementary school level students in Putuk Hamlet. This free tutoring has a significant level of effectiveness in improving learning outcomes and overcoming problems in student learning.